2007
DOI: 10.3748/wjg.v13.i26.3540
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic liver disease of obesity and role of adipose tissue in the pathogenesis of nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is an increasingly recognized cause of liver-related morbidity and mortality. It can develop secondary to numerous causes but a great majority of NAFLD cases occur in patients who are obese or present with other components of metabolic syndrome (hypertension, dyslipidemia, diabetes). This is called primary NAFLD and insulin resistance plays a key role in its pathogenesis. Obesity is characterized by expanded adipose tissue, which is under a state of chronic inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
171
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(183 citation statements)
references
References 211 publications
9
171
0
3
Order By: Relevance
“…Third, the smoking data was collected by binary criteria in this study so the effects of smoking on metabolic syndrome components might be underestimated [35] . In summary, fatty liver and smoking were closely related to insulin resistance [1][2][3][4][5][6][7][8][9][11][12][13][14]16,[21][22][23]25,32] , and our study provided evidence that fatty liver and smoking had a synergistic effect on metabolic syndrome and its components, especially for triglyceride and HDL-C levels. We suggested that smoking cessation would have the great benefit of reducing the risk of metabolic syndrome, especially for subjects with fatty liver.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Third, the smoking data was collected by binary criteria in this study so the effects of smoking on metabolic syndrome components might be underestimated [35] . In summary, fatty liver and smoking were closely related to insulin resistance [1][2][3][4][5][6][7][8][9][11][12][13][14]16,[21][22][23]25,32] , and our study provided evidence that fatty liver and smoking had a synergistic effect on metabolic syndrome and its components, especially for triglyceride and HDL-C levels. We suggested that smoking cessation would have the great benefit of reducing the risk of metabolic syndrome, especially for subjects with fatty liver.…”
Section: Discussionmentioning
confidence: 55%
“…The association between fatty liver and metabolic syndrome was broadly discussed in previous studies [1][2][3][4][5][6][7][8][9] . Fatty liver is often associated with central obesity, type 2 diabetes mellitus, dyslipidemia, and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Besides excessive non-esterified fatty acid influx, mediating factors may include: (i) components of the metabolic syndrome (14,15); (ii) cytokines (16)(17)(18)(19)(20)(21)(22)(23)(24) and (iii) mitochondrial dysfunction (25) (Fig. 1).…”
Section: Aetiologymentioning
confidence: 99%
“…Because secreted proteins are also involved in the progression of cardiovascular disease and cancer, there is significant interest in mining the secretome for novel biological markers (5). Whereas endocrine organs specialize in the secretion of proteins into circulation, there is mounting evidence that adipose tissue and skeletal muscle constitutively or intermittently secrete bioactive proteins (6,7). In this study, we hypothesized that skeletal muscle of extremely obese and insulinresistant women would secrete proteins into circulation that act as prognostic or diagnostic biomarkers of obesityassociated comorbidities.…”
mentioning
confidence: 99%